Prospective rates of suicide attempts and nonsuicidal self-injury by young people with bipolar disorder participating in a psychotherapy study. (February 2016) - Inder, Maree L; Crowe, Marie T; Luty, Suzanne E; Carter, Janet D; Moor, Stephanie; Frampton, Christopher M; Joyce, Peter R
Objective: Bipolar disorder is a chronic relapsing disorder associated with high rates of suicide, suicide attempts and nonsuicidal self-injury. The study aimed to prospectively identify the rates of suicide attempts and nonsuicidal self-injury in young people participating in an adjunctive randomised controlled psychotherapy for bipolar disorder and to identify differences in individuals who engaged in nonsuicidal self-injury, made suicide attempts or did both. Method: In all, 100 participants aged 15–36 years with bipolar disorder received 78 weeks of psychotherapy and were followed up for a further 78 weeks. Data were collected using the Longitudinal Interval Follow-up Evaluation. Results: Suicide attempts reduced from 11% at baseline to 1% at the end of follow-up (week 156). Similarly, self-harm reduced from 15% at baseline to 7% at the end of follow-up. Individuals who engaged in both nonsuicidal self-injury and made suicide attempts differed from those with who only made suicide attempts, engaged in nonsuicidal self-injury or did neither. They were characterised by a younger age of illness onset and higher comorbidity. Conclusion: Adjunctive intensive psychotherapy may be effective in reducing suicide attempts and nonsuicidal self-injury and warrants further attention. Particular attention needs to be paid to individuals with early age of onset of bipolar disorder.